(untitled) (CIPEEX, 2022)
OBJECTIVES: THIS STUDY AIMED TO IDENTIFY ASPECTS RELATED TO THE INCIDENCE OF SELF-MEDICATION TO RELIEVE GASTROINTESTINAL SYMPTOMS IN MEDICAL STUDENTS AT UNIEVANGLICA. THE SPECIFIC OBJECTIVES OBJECTIVES OF THIS STUDY WERE TO IDENTIFY WHICH MEDICATIONS ARE MOST USED IN SELF-MEDICATION, TO IDENTIFY THE PROFILES OF RESPONDENTS BY DIFFERENTIATING GENDER, AGE AND PERIOD THAT THE STUDENT IS STUDYING WITH SELF-MEDICATION, AND ALSO TO VERIFY THE INFLUENCE OF THE KNOWLEDGE ACQUIRED BY MEDICAL STUDENTS IN THE COURSE OF UNIEVANGLICA’S MEDICINE IN SELF-MEDICATION. METHODES: THIS IS A CROSS-SECTIONAL, DESCRIPTIVE AND QUANTITATIVE STUDY. DATA WERE COLLECTED THROUGH A QUESTIONNAIRE APPLIED IN 2022 AMONG &NBSP;MEDICAL STUDENTS AT UNIEVANGLICA FROM THE FIRST TO THE EIGHTH PERIOD. THE SAMPLE WAS FOR CONVENIENCE AND HAD THE PARTICIPATION OF 173 STUDENTS FROM A POPULATION OF APPROXIMATELY 800. THE SAMPLE POWER WAS CALCULATED, POST HOC, BASED ON THE STATISTICAL TEST USED (CHI-SQUARE), AVERAGE EFFECT SIZE OF 0.3 AND SIGNIFICANCE LEVEL OF 5%, WITH A POWER OF 82%. 184 QUESTIONNAIRES WERE APPLIED AND 11 WERE EXCLUDED DUE TO INCOMPLETE SAMPLE DATA, QUESTIONNAIRES NOT ANSWERED CORRECTLY AND UNDER 18 . RESULTS: DATA WERE OBTAINED FROM 173 PARTICIPANTS, OF WHICH 72.8% WERE WOMEN AND THE MEAN AGE WAS 21.5 YEARS. AMONG THE SYMPTOMATIC, 78.6% HAD BURNING. AMONG MEDICINES, 71.1%. USED ANTACIDS. IN 62.9% THE KNOWLEDGE ACQUIRED IN THE TRAINING INFLUENCED THE TIME OF SEEKING THE DOCTOR AND 66.5% SELF-MEDICATED FOR GASTROINTESTINAL SYMPTOMS. THERE WAS A PREDOMINANCE OF FEMALES, IN WHICH 77.5% OF WOMEN SELF-MEDICATE, WHILE 62.3% OF MEN PERFORM THIS PRACTICE. AS A PERCENTAGE, THE 8TH PERIOD SELF-MEDICATES MORE (80%). 53.4% €‹€‹OF RESPONDENTS DENIED THAT THEIR ACQUIRED KNOWLEDGE IS LINKED TO SELF-MEDICATION, AND IN THE 8TH PERIOD 75% RESPONDED THAT THERE IS INFLUENCE. 53.6% CLAIMED THAT THE ACQUIRED KNOWLEDGE INFLUENCED THE CHOICE OF MEDICATION TO SELF-MEDICATE. CONCLUSION: THE PRESENT STUDY SHOWED WHICH DRUGS ARE MOST COMMONLY USED TO TREAT GASTROINTESTINAL SYMPTOMS, THESE, ANTACIDS ARE FIRST FOLLOWED BY PROTON PUMP INHIBITORS (IBPS). THE PRESENT STUDY ALSO PRESENTED, THROUGH THE COLLECTED DATA, THAT SELF -MEDICATION DOES NOT NECESSARILY INCREASE IN PROPORTION TO THE KNOWLEDGE OBTAINED THROUGHOUT THE COURSE, BUT DEMONSTRATES THAT THE ACQUIRED KNOWLEDGE INFLUENCES THE MEDICINE TO BE USED FOR SELF -MEDICATION, AS WELL AS INFLUENCED THE MOMENT OF SEEKS TO THE MEDICAL PROFESSIONAL. THUS, THE KNOWLEDGE ACQUIRED THROUGHOUT THE COURSE HAS RELEVANCE IN FACTORS THAT DO NOT NECESSARILY RELATE TO THE ACT OF SELF-MEDICATION. THEREFORE, THERE IS A CLEAR NEED TO DEEPEN THE THEME OF SELF-MEDICATION IN UNDERGRADUATE MEDICAL STUDENTS, SO THAT STUDENTS CAN CLEARLY UNDERSTAND THE RISKS INHERENT IN THIS PRACTICE.